KEBERLAKUAN PERATURAN DAERAH KOTA SURABAYA NOMOR 1 TAHUN 2016 TENTANG RETRIBUSI PENGOLAHAN LIMBAH CAIR DALAM BENTUK TINJA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 2022 TENTANG HUBUNGAN KEUANGAN ANTARA PEMERINTAH PUSAT DAN PEMERINTAH DAERAH - Ayu Wulandari; Mohammad Saleh (Jurnal HUKUM BISNIS, 2023)
Prior to the enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, Surabaya City Regional Regulation Number 1 of 2016 concerning Levies for Processing Liquid Waste in the Form of Feces was officially valid and binding in the City of Surabaya with reference to Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. This paper aims to find out the enactment of Surabaya City Regional Regulation Number 1 of 2016 concerning Retribution for Liquid Waste Treatment in the Form of Feces after the enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. The focus of this study is to analyze the legal status of Surabaya City Regional Regulation Number 1 of 2016 concerning Retribution for Liquid Waste Treatment in the Form of Feces after the enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments; and to analyze the legal norms in the Regional Regulation of the City of Surabaya Number 1 of 2016 concerning Levies for the Treatment of Liquid Waste in the Form of Feces which are no longer in accordance with Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. The research method uses normative legal research, using a statutory approach (statue approach) and a conceptual approach (conceptual approach). The collection of legal materials is carried out through literature review, both primary and secondary legal materials. The result of the research is that the legal status of the Liquid Waste Treatment levy is still valid and it is possible to collect it. Contextually, the Feces Liquid Waste Treatment Retribution is interpreted as part of the category of cleaning services in the General Services Retribution so that the Regional Regulation of the City of Surabaya Number 1 of 2016 is declared to remain valid and valid and juridically the regulated norms are still in accordance with Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, but adjustments still need to be made, especially the formulation of the calculation of fees taking into account economic principles and the intended adjustments are stipulated in the form of a Regional Regulation.Keywords: Regional finances, regional fees, and waste